Analisis Faktor-Faktor Yang Mempengaruhi Minat Beli Konsumen Dalam Membeli Rumah Di Kota Batam - Nora Pitri Nainggolan; Heryenzus Heryenzus (JURNAL ILMIAH MANAJEMEN & BISNIS, 2018)
The purpose of this study is to determine whether the factors that can be used for the purchase of houses in the city of Batam. This study uses multiple linear regression analysis with SPSS Version 20 program. Population which is society of Batam City. The sample used is 399 people with proportional sampling method. The results show that the quality of products to buy consumers in buying a house in the City of batamuling significant. The influence of prices on consumers in buying a home in Batam City is significant. The partial influence of location on consumer interest in buying a house in Batam City is significant. The effect of partial promotion on consumer interest in buying a house in Batam City has a significant effect. And requirements have a significant effect on product quality, price, location, promotion to consumer purchase in buying house in Batam City.